2016
DOI: 10.1111/sode.12212
|View full text |Cite
|
Sign up to set email alerts
|

Different ways of knowing a child and their relations to mother‐reported autonomy support

Abstract: We considered how different forms of child knowledge (i.e., mothers'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Such a radical perspective would not only be pragmatically naïve, it would also be theoretically inconsistent with the very idea of what need-supportive socializing agents do. That is, inherent to the practice of need support is that socializing agents take both personal characteristics (e.g., personality, preferences) and situational circumstances into account to maximize participants' need-satisfying experiences (Mabbe et al 2020;Mageau et al 2017). Thus, need-supportive socialization implies ongoing calibration of one's approach to others (Vansteenkiste et al 2019).…”
Section: Advancementsmentioning
confidence: 99%
“…Such a radical perspective would not only be pragmatically naïve, it would also be theoretically inconsistent with the very idea of what need-supportive socializing agents do. That is, inherent to the practice of need support is that socializing agents take both personal characteristics (e.g., personality, preferences) and situational circumstances into account to maximize participants' need-satisfying experiences (Mabbe et al 2020;Mageau et al 2017). Thus, need-supportive socialization implies ongoing calibration of one's approach to others (Vansteenkiste et al 2019).…”
Section: Advancementsmentioning
confidence: 99%
“…Within SDT, the organization of behavior has always been deeply conceptualized in terms of people’s natural and spontaneous integrative tendencies to engage, assimilate, and connect. Simultaneously, SDT also concerns the factors in physical (e.g., Chen, Van Assche et al, ; Weinstein & Stone, ) and social (e.g., Mageau, Sherman, Grusec, Koestner, & Bureau, ) environments that facilitate or inhibit these tendencies. In addressing these issues, SDT has in an abiding way embraced empirical approaches, and the goal of fitting its methods and findings into the larger framework of the life sciences (Ryan & Deci, ).…”
Section: Sdt As An Evolving Theoretical Frameworkmentioning
confidence: 99%
“…But the use of other methods and designs is abundant. The SDT literature is replete with experimental (e.g., Benita, Shane, Elgali, & Roth, ; Deci et al, ; Wuyts, Vansteenkiste, Mabbe, & Soenens, ), longitudinal (e.g., Mageau et al, ), and experience‐sampling studies (Ryan, Bernstein, & Brown, ; Thomaes, Sedikides, van den Bos, Hutteman, & Reijntjes, ), and SDT studies make use of a variety of “third person” and non‐self‐report methods including behavior observations (e.g., Ahmad, Vansteenkiste, & Soenens, ; Haerens et al, ), (neuro)physiological assessments (e.g., Reeve & Tseng, ), priming procedures (e.g., Radel, Sarazin, & Pelletier, ; Weinstein, Hodgins, & Ryan, ), and implicit measures (e.g., Ryan & Grolnick, ; Van Assche, Van der Kaap‐Deeder, De Schryver, Audenaert, & Vansteenkiste, ). SDT thus has always been based on convergent sources of evidence that include both objective methods as well as the important information that can come from self‐reports and third‐party ratings (e.g., Ratelle, Morin, Guay, & Duchesne, ).…”
Section: On the Interface Between Sdt And Psimentioning
confidence: 99%
“…Parents who take the perspective of their children have a better chance of identifying misunderstandings or reasons for misbehavior and, therefore, a better chance of engaging in interventions that will facilitate compliance. Mothers of young adolescents who reported that they took the perspective of their adolescent, for example, increased their autonomy supportive behavior over the course of 2 years (Mageau, Sherman, Grusec, Koestner, & Bureau, in press). Lundell, Grusec, McShane, and Davidov (2008), asked adolescents to talk about recent disagreements they had had with their mothers and to say what they had hoped to accomplish during the disagreement.…”
Section: Core Skills In the Administration Of Disciplinementioning
confidence: 99%